2022
DOI: 10.1177/02601060211072370
|View full text |Cite
|
Sign up to set email alerts
|

Social Influence on Fad Diet Use: A Systematic Literature Review

Abstract: Background: A fad diet is a broad term used to describe dieting methods that recommend altering the intake of macronutrients to specific proportions or instruct people to intake or avoid particular foods, often with the goal of rapid weight loss. Previous literature reviews report social influence impacts general diet behaviour, but have yet to examine fad diets, specifically. Therefore, the purpose of this systematic review was to synthesize literature related to social influence on an individual's fad diet u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 71 publications
(146 reference statements)
1
5
0
Order By: Relevance
“…In contrast, a negative relationship is obtained between adherence to the Mediterranean diet and mass media pressure, these results being similar to those obtained by Marfil-Carmona et al (2021). In view of these findings, Zou et al (2020) argue that the media have a powerful reach, but Spadine and Patterson (2022) point out that the nutritional messages they convey are mostly erroneous, with a predominance of advertisements for unhealthy and pre-cooked products, as well as a bias towards diets based on calorie imbalance.…”
Section: Discussionsupporting
confidence: 67%
“…In contrast, a negative relationship is obtained between adherence to the Mediterranean diet and mass media pressure, these results being similar to those obtained by Marfil-Carmona et al (2021). In view of these findings, Zou et al (2020) argue that the media have a powerful reach, but Spadine and Patterson (2022) point out that the nutritional messages they convey are mostly erroneous, with a predominance of advertisements for unhealthy and pre-cooked products, as well as a bias towards diets based on calorie imbalance.…”
Section: Discussionsupporting
confidence: 67%
“…In this age of widespread smartphone penetration and social media influence, people with overweight and obesity are often exposed to fad diets (eg, ketogenic diet, intermittent fasting, and Atkins diet) [ 44 ], and popular physical activities such as high-intensity interval training, cardio training, and resistance training. However, studies have shown limited effects and potential health issues (eg, malnutrition, dehydration, and acute injuries) with such diets [ 45 ] and unsupervised intensive physical activities [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diets Disguised as Lifestyles. Diet programs gained increasing popularity during the later 20 th century (Spadine & Patterson, 2022). Weight Watchers, Atkins, Jenny Craig, and South Beach were among the frontrunners of weight loss prescriptions (Harrison, 2019).…”
Section: Background and Historymentioning
confidence: 99%